The relationship between driving distance and different types of contraction in core muscles in Korea elite female golfers - Lee, J.-B.; Sung, B.-J.; Seo, T. B. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: This study compared and examined the relationship between the concentric, eccentric, and isometric muscular contraction measurements that are commonly used to assess trunk strength and power, and the driving distance in elite female golfers. The purpose of this study was to utilize as a basis to evaluate the driving distance-related physical training program design and its efficacy. METHODS: Eighteen female golfers from A club in Gyeonggi province are recruited. The driving distance, medicine ball throwing, isokinetic trunk flexor, and extensor strength and power, and isometric strength in the 3D electromagnetic motion analysis system were assessed. The statistical analysis adopted the Students` t-test to adjust the different units in each assessment method, and then interrelation and correlation analysis between the driving distance was conducted. RESULTS: The result of this study is as the following: the medicine ball throwing, isokinetic trunk extensor power, isometric trunk flexor, and extensor strength, and left and right flexor and rotator strength showed high correlation with the driving distance. In the comparison between strength factors, isokinetic trunk extensor strength had a high correlation (R2=0.452), while the medicine ball throw and isokinetic trunk extensor power were reported a higher correlation in order (R2=0.740). In the overall comparison analysis, the isometric trunk left rotation, and isometric trunk extensor had an R2 value of 0.893. CONCLUSIONS: Consequently, the isometric trunk rotational strength and extensor strength had the highest correlation with the driving distance. This result can be used to design the physical fitness program for golfers.